The role of Akkermansia muciniphila in the regulation of inflammatory bowel disease: intestinal immunity and metabolism - Xu, Wang; Li, Aijing; Jing, Huijuan; Zhang, Xiaoping; Dong, Xucheng; Song, Zhiqiang; Wu, Nanping; Zheng, Shufa (Frontiers in Immunology, 2025)
Inflammatory bowel disease (IBD) is closely associated with the abundance of Akkermansia muciniphila (A. muciniphila), a resident member of the intestinal tract that is being developed as a next-generation probiotic. Accumulated evidence has indicated that the live and pasteurized A. muciniphila, as well as its components and secretions, have exhibited protective and ameliorative functions in IBD. Nevertheless, the precise and intricate regulatory mechanisms of A. muciniphila in IBD remain unclear, which is crucial for investigating the etiology of IBD and searching for innovative, targeted therapeutic strategies. In this review, we discuss the reciprocal influence between A. muciniphila and intestinal immunity in IBD, encompassing the roles of immune cells, intestinal epithelial cells (IECs), and intestinal stem cells (ISCs). Subsequently, we outline the mutual regulatory interactions between A. muciniphila and intestinal metabolism, focusing on tryptophan (Trp) metabolism, short-chain fatty acids (SCFAs) metabolism, and bile acids (BAs) metabolism. Understanding how A. muciniphila interacts with its host is a vital step for facilitating its application in IBD therapy.